A QUALITATIVE STUDY OF DIETARY EXCLUSION OF MILK, SUGAR, WHEAT, AND SOYA ON CHILDREN WITH NEURODEVELOPMENTAL DISORDERS - Shabeeda .P; Sharma, Megha Manish (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The impact of eliminating milk, sugar, wheat, and soy from the diets of 110 children at the Ardra Foundation who have neurodevelopmental disorders (NDDs) are assessed in this qualitative study. Children with autism (10), ADHD (50), ADD (10), and specific learning disorders (SLD: 40) were among the participants. Significant gains in speaking, emotional control, attention, sleep pattern and anxiety reduction were seen in the data gathered from caregiver interviews and behavioral observations. The approach, results, and consequences of dietary treatments in the management of symptoms of NDD are described in this article.